Pengaruh Motivasi dan Pengalaman Kerja terhadap Produktivitas Karyawan di Kantor Regional VI BKN Kota Medan - Vikro Gabriel V. Saing; Asriyana S. Kaseng; Denni Denni; Iventura Fitra Uli Tamba; Debora Tambunan (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to assess the impact of motivation and work experience on employee productivity at the Regional Office VI of the State Civil Service Agency of Medan City. Motivation and work experience are considered crucial factors that can affect individual performance in an organization. The method used in this study is quantitative with data collection through questionnaires distributed to 81 employees in the office. The collected data were then analyzed using multiple regression analysis techniques to identify the relationship between motivation variables, work experience, and work productivity. The results of the study revealed that both variables, namely motivation and work experience, have a positive influence on work productivity. High motivation encourages employees to work more efficiently, as well as the work experience variable. With relevant work experience, employee productivity at the Regional Office VI of the State Civil Service Agency of Medan City can be increased. The results of this study also provide insight for leaders in designing human resource development strategies that can increase productivity with a focus on increasing motivation and work experience. The suggestions presented in this study are the need for ongoing training and award programs that can increase motivation and utilize work experience to achieve more optimal results.